Neutrality of The State Civil Apparatus (ASN) in Indonesian Elections - Muhammad Ruslihardi; Adinda Ramadhani; Siska Wirawati; Tuty Ardian Rahmah; Fajarwaty Kusumawardhani; Sri Roserdevi Nasution; Harcini Harcini (JOELS: Journal of Election and Leadership, 2021)
The neutrality of ASN has always been a hot topic in various circles. Concern over the alignment of ASN to one of the candidate pairs is the main reason there are three types of politicization of the bureaucracy in Indonesia: First, openly politicization. Second, semi-open politicization, third, closed politicization. By utilizing the votes of civil servants, it is obvious for incumbent candidates with the promise of being given a position or to support their superiors and the mobilization of civil servants during general and regional elections. The politicization of the bureaucracy in Indonesia is still exist, currently politicization can appear from the legislature or from the executive with the aim of perpetuating power. From symptoms ranging from users of state facilities, mobilization of civil servants, compensation for positions, commercialization of positions, recruitment of new civil servants, to removal (depromotion) of regional secretaries. The involvement of the State Civil Apparatus (ASN) in practical politics is obvious because ASN is considered as the easiest way to influence society. The position of ASN is quite strategic and seen in the community, of course, will make it easier for candidates to gain support and have big hopes in the pilkada. The non-neutrality of ASN is certainly in the spotlight amidst the hopes of the community that ASN is able to become a pillar of an example of an honest and fair course of democratization.